Implementasi Senam Komering untuk Meningkatkan Kebugaran Jasamani dan Pelestarian Budaya Lokal di Program Studi Pendidikan Olahraga Universitas Bina Darma - umam, said afil; Sukmawati, Noviria (Universitas Negeri Gorontalo, 2025)
This community service program aimed to implement Komering Gymnastics as a culture-based physical exercise model to improve students’ physical fitness while fostering awareness of local cultural preservation. The program was conducted at Universitas Bina Darma, involving students of the Physical Education Study Program as the target community. The activities were carried out routinely every Friday through several stages, including the socialization of Komering culture, gymnastics training, movement demonstrations, and direct practice integrated into campus activities. Program evaluation was conducted using simple methods, such as observing participation levels, students’ ability to perform the movement sequences, and reflective feedback on cultural understanding. The results indicated a high level of student participation and improvements in coordination, flexibility, and physical endurance through continuous practice of Komering Gymnastics. In addition, students demonstrated increased understanding and awareness of the importance of preserving Komering culture as part of local wisdom. This community service activity contributed positively to addressing partner-related issues, namely the limited availability of culture-based physical exercise and the low level of students’ knowledge of local culture. The implementation of Komering Gymnastics serves as an educational and culturally valuable alternative for physical fitness activities in academic settings and is recommended for sustainable development in physical education learning and similar community service programs.